2020
DOI: 10.3390/ijerph17155393
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Negative Emotions Pre- and Post-Implementation of Graphic Health Warnings: Longitudinal Evidence from South Korea

Abstract: This longitudinal study investigated the factors that determine the effectiveness of graphic health warnings (GHWs) by comparing 246 South Korean smoker’s responses before and after the introduction of the country’s new tobacco control policy wherein GHWs were placed on all cigarette packaging. Even though introducing GHWs did not cause immediate changes in smokers’ intention to quit smoking or perception of smoking’s health risk, GHWs eventually motivated smokers to quit smoking when they experienced negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
1
0
0
Order By: Relevance
“…The findings of this study were consistent with those of earlier studies, which suggests that GHWL are positively associated with reducing smoking in adolescents (16,(21)(22)(23). Other studies conducted on Korean adolescents or adults also revealed that GHWL can be an effective way to prevent smoking (16,(24)(25)(26)(27). Smokers who noticed the warnings were significantly more likely to disclose associated health risks.…”
Section: Discussionsupporting
confidence: 90%
“…The findings of this study were consistent with those of earlier studies, which suggests that GHWL are positively associated with reducing smoking in adolescents (16,(21)(22)(23). Other studies conducted on Korean adolescents or adults also revealed that GHWL can be an effective way to prevent smoking (16,(24)(25)(26)(27). Smokers who noticed the warnings were significantly more likely to disclose associated health risks.…”
Section: Discussionsupporting
confidence: 90%